Penerapan Terapi Murottal pada Asuhan Keperawatan Ibu Postpartum Sectio Caesarea atas Indikasi Retensio Plasenta - Annisa Nur Arianti; Merida Simanjuntak (AKPER Pasar Rebo, 2023)
Background: Childbirth is a natural process to give birth to the results of full-term conception in the form of a fetus and placenta. Sectio caesarea delivery is generally done when the normal delivery process through the vagina is not possible because of the risk of complications in the mother or fetus. Placental retention is the detachment of the placenta beyond half an hour after the baby is born or the condition of the placenta has been partially detached so that it requires manual placental action immediately. Objective: this study aims to reduce pain in postpartum sectio caesarea patients with murothal therapy. Method: descriptive research with case study approach and literature accompanied by the application of evidence-based practice in postpartum sectio. Murothal distraction therapy is carried out for 15-20 minutes when pain appears and after 2 hours of analgetic administration, therapy is carried out for three days to reduce the intensity of patient pain. Results: showed a significant decrease in pain intensity score from pain scale 6 to pain scale 3 on day three. Conclusion: Murottal therapy is one of the non-pharmacological therapies with distraction techniques that can reduce pain scales in postpartum patients with pain problems due to surgery.